'Sharing expertise with the public': The production of communicability and the ethics of media dialogical networking. (March 2022) - Smith, Simon
Highlights: How experts talk publicly about mental illness is a longstanding ethical concern. Experts are communicable in two different ways – reportability and tellability. Media dialogical networks are integrated categorially and narratively. Media dialogical networking involves trade-offs between tellability and reportability. Narrative translations of dialogical networks can reorder membership categories. Abstract: This paper examines two controversies implicating psychiatrists in order to shine a light on the ethics of experts' media dialogical networking. Employing a dual approach to discourse underpinned by membership categorisation and narrative analysis, and making a corresponding distinction between communicability as reportability and as tellability, I show that MDNs are not just sequences of arguments and counter-arguments, but also sequences of happenings that redefine situations and reposition actors. In the cases examined, each expert is accused of inappropriate behaviour – public talk unbecoming of experts. I reconstruct the interactive negotiations around communication ethics between experts and journalists in interviews and show how these interactions and the distributed reactions they provoked elsewhere in the controversy-related MDNs were narrativised in summarising news reports and interview introductions, positioning experts more as protagonists than as category incumbents. Taking media dialogical networking as social practice and performative discursive repertoire, I show how its dual – narrative-routine – performance involves trade-offs between reportability and tellability, rendering problematic any simple rule covering experts' voice entitlements, i.e. knowing when, where and how it is appropriate to offer a professional opinion. The public conversation about mental illness, however, is enriched by these imbrications.